27th December: 1st Sunday of Christmas - Down, Martin (The expository times, 2015)
The article presents the author's reflection on the gosphel sermon for the 1st Sunday of Christmas season from the book of Luke, Chapter 2, Verses 41-52 focuses on the childhood of Jesus. The author cites the childhood life of Jesus as a carpenter's son such as Jesus learning and developing skills in carpenting. He also emphasizes on the role of parents in developing their children's personal and interpersonal skills and learning.